Checklist of the vascular alien flora of Catalonia (northeastern Iberian Peninsula, Spain) - Aymerich, Pere; Sáez, Llorenç (Mediterranean Botany, 2019)
This is an inventory of the vascular alien flora of Catalonia (northeastern Iberian Peninsula, Spain) updated to 2018, representing 1068 alien taxa in total. 554 (52.0%) out of them are casual and 514 (48.0%) are established. 87 taxa (8.1% of the total number and 16.8 % of those established) show an invasive behaviour. The geographic zone with more alien plants is the most anthropogenic maritime area. However, the differences among regions decrease when the degree of naturalization of taxa increases and the number of invaders is very similar in all sectors. Only 26.2% of the taxa are more or less abundant, while the rest are rare or they have vanished. The alien flora is represented by 115 families, 87 out of them include naturalised species. The most diverse genera are Opuntia (20 taxa), Amaranthus (18 taxa) and Solanum (15 taxa). Most of the alien plants have been introduced since the beginning of the twentieth century (70.7%), with a strong increase since 1970 (50.3% of the total number). Almost two thirds of alien taxa have their origin in Euro-Mediterranean area and America, while 24.6% come from other geographical areas. The taxa originated in cultivation represent 9.5%, whereas spontaneous hybrids only 1.2%. From the temporal point of view, the rate of Euro-Mediterranean taxa shows a progressive reduction parallel to an increase of those of other origins, which have reached 73.2% of introductions during the last 50 years. The most important way of introduction is gardening (58.0%), followed by agriculture and commerce, while forestry is marginal. Invasive taxa mainly come from gardening and trade, but the proportion of the latter that become invasive is higher (6.1% and 15.6%, respectively). Most of the established aliens are annual and perennial forbs, while other biological types are less represented. Annual and perennial forbs are also dominant among the invasive alien species, although there is a noticeable increase of trees and climbers.